Fire scars in Prosopis caldenia wood in Luán Toro, La Pampa province, Argentina - Medina, Andrea A. (Bosque (Valdivia), 2008)
Fire is a significant component of the disturbance regime that affects Prosopis caldenia (caldén) woodlands with ecological and economical importance. Obtaining information on its temporal and spatial dynamics would be of great importance for management planning and rational use of these forests. The dating of fire scars registered in tree trunks is a widely used method for reconstructing fire regimes in forested areas. In this paper fire scars registered in the wood of caldén trees were analyzed from an area that was affected by prescribed fires to enhance pastures for livestock. Other marks, tree growth rings and structures associated to this disturbance are described. Although fire scars allow precise knowledge of the frequency and seasonality of past fires, the analysis of other structures associated to the influence of fire, such as ring separation, fire marks, “micro-rings” and rings with bands of parenchymatous tissue, would provide greater information on some immediate characteristics of fire regimes, such as intensity and spatial extent.